An Intervention to Support Elementary School Faculty in Meeting the Needs of Transgender and Gender Non-Conforming Students. Issue 3 (1st September 2020) - Springer, Sarah I.; Mason, Erin C. M.; Moss, Lauren J.; Pugliese, Ashley; Colucci, Jessica
ABSTRACT: Transgender students represent a population at great risk for mental health concerns, and school counselor prevention efforts are key in supporting their healthy development. Results of this Consensual Qualitative Research (CQR) study following an elementary staff presentation supporting trans youth suggest that contextual factors, professional identity, and presentation format contributed to participants' openness and interest in learning more about the needs of this population. Implications for school counselor practice and preparation are provided.